The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1516-35982003000200008
|View full text |Cite
|
Sign up to set email alerts
|

Objetivos econômicos de seleção de bovinos de leite para fazenda demonstrativa na Zona da Mata de Minas Gerais

Abstract: RESUMO -Os valores econômicos para características de gado de leite foram calculados a partir de dados econômicos e zootécnicos do Sistema de Produção de Leite a Pasto com Gado Mestiço da Embrapa Gado de Leite. Estes valores foram estimados por dois métodos: 1) utilizando a derivada parcial do lucro com respeito a cada característica e 2) pela derivada parcial da razão receita/custo, para cada característica, ambas as derivadas avaliadas no valor médio das outras características. Com este último método, os val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…It is noteworthy that the selection for weight may not be favorable due to the fact that, in some cases, the sale of cull cow may not cover this category of animals (Martins et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the selection for weight may not be favorable due to the fact that, in some cases, the sale of cull cow may not cover this category of animals (Martins et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Orientação similar tem sido apontada, indicando que a diminuição do tamanho seria um fator importante para os sistemas de produção de leite do Brasil (MARTINS et al, 2003).…”
Section: Resultsunclassified
“…Martins et al (2003) showed that about 44% of feed costs were due to cow maintenance. The energy spent in increased maintenance is not compensated by the increase in meat sold (Cardoso et al, 2004).…”
Section: Resultsmentioning
confidence: 99%